Pornografi Iklan Obat Pembesar Alat Vital di Media Sosial dalam Tinjauan Etika Pariwara Indonesia - Anisa Ambar Jati; Raisa Fatihah; Yuyun Sulistyowati; Dhimas Aryo Vipha Ananda (ANALOGI Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines violations of the Indonesian Advertising Ethics in advertisements for male enhancement products on social media, specifically on Platform X). These advertisements feature exaggerated claims about sexual performance enhancement and visuals containing elements of sexual exploitation. A qualitative descriptive method was employed to analyze the advertisement content and identify ethical breaches based on the Indonesian Advertising Ethics guidelines, the Electronic Information and Transactions Law, and regulations from the Food and Drug Administration. The findings reveal that these advertisements utilize hyperbolic language, unsubstantiated claims, and inappropriate visualizations to attract consumers. Such practices violate the Indonesian Advertising Ethics provisions regarding the use of language and visuals in advertisements. This study underscores the importance of adherence to advertising regulations to protect consumers from misleading information while maintaining ethics and credibility in marketing practices.